Analisis Kesantunan Berbahasa dalam Film Animasi Nussa dan Rara Dimanfaatkan sebagai Bahan Ajar Pelajaran Bahasa Indonesia di SMA Kelas XII - Nur Alvi Lael; Oding Supriadi; Sahlan Mujtaba (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to describe the results of the analysis of politeness in the language of the animated film Nussa and Rara regarding the principles of politeness. The subject of this research was the animated film Nussa and Rara. Meanwhile, the object in this study is the form of speech that contains language politeness and analyzes the indicators of the maxim of politeness in language which are suspected of having compliance and violating the principles of language politeness as conveyed by Leech. The type of research used in this research is descriptive qualitative. The data collection of this research was carried out using the look method. The listening technique used is listening to the language used by speakers to study the language, then using an advanced technique, namely the free-engage-talk listening technique, meaning that the researcher only acts as an observer of language use. The results showed that most of the speeches contained in the animated film Nussa and Rara contain the principles of politeness in language, both the maxim of generosity, maxim of consensus, maxim of wisdom, maxim of appreciation, maxim of sympathy, maxim of simplicity. However, there is also 1 utterance that violates the maxim of consensus, 2 utterances that violates the maxim of simplicity, and 1 utterance that violates the maxim of generosity. The results of the analysis of the animated film Nussa and Rara will be used as teaching materials in schools in learning politeness in high school language class XII in the language specialization class.